The correlation between electronic structure and antimalarial activity of alkoxylated and hydroxylated chalcones - Batagin-Neto, Augusto [UNESP]; Lavarda, Francisco Carlos [UNESP] (Springer Nature, 2013)
Chalcones have shown potential to several pharmacological applications including antimalarial properties. We employed multivariate data analysis to correlate the antimalarial activity with electronic structure descriptors obtained through quantum mechanical calculations. The results show high statistical significance and bring valuable insights in order to design new compounds. © 2013 Springer Science+Business Media New York.
Keywords: Antimalarials; Chalcones; Electronic structure; Molecular modeling